Neuropathic Pain and Sleep: A Review. Issue 1 (December 2017) - Ferini-Strambi, Luigi
Abstract Neuropathic pain is associated with sleep disturbances, and in turn poor sleep quality leads to increased pain sensitivity, so it is essential to assess sleep alongside neuropathic pain. Responses to drugs are inconsistent and identifying the best treatment option that will reduce pain and improve sleep quality remains challenging for clinicians. Anticonvulsants such as pregabalin and gabapentin improve neuropathic pain and have a positive effect on comorbid sleep disturbances. Opioids and antidepressants are effective in reducing pain but can exacerbate sleep disturbances. Funding : Pfizer, Italy.